Cognitive Enhancers in Schizophrenia: A Systematic Review and Meta-Analysis of Alpha-7 Nicotinic Acetylcholine Receptor Agonists for Cognitive Deficits and Negative Symptoms - Recio-Barbero, María; Segarra, Rafael; Zabala, Arantzazu; González-Fraile, Eduardo; González-Pinto, Ana; Ballesteros, Javier (Frontiers in Psychiatry, 2021)
Background: Schizophrenia is a severe and enduring disease and one of the leading causes of disability worldwide. Cognitive impairment is a core clinical symptom that plays a crucial role in functional outcomes and prognosis, thus making it a relevant treatment target. The aim of this study was to assess the efficacy of α-7 nicotinic acetylcholine receptor agonists (α-7 nAChR) as adjunctive treatment to enhance cognition and ameliorate negative symptoms in patients with schizophrenia. Methods: A search strategy was developed for Medline, Embase, and the Cochrane Central Register of Controlled Trials up to May 2019. We included randomised controlled trials (RCTs) that compared antipsychotic treatment plus α-7 nAChR agonists with antipsychotic treatment plus placebo and determined their effects on the main cognitive domains proposed by the MATRICS initiative and on negative symptoms. Two authors independently reviewed study eligibility, data extraction, and assessed the risk of bias of the studies included. According to the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework, we used a random-effects model and assessed the quality of the evidence. Results: Thirteen studies were included in the quantitative analysis. No differences were found in any of the cognitive domains assessed in 4 RCTs (n=414). In contrast, 9 RCTs (n= 978) presented a small effect in support of α-7 nAChR agonists for negative symptoms (standardized mean difference –0.28, 95% CI [–0.56 to –0.00]; p value=0.05), even though the confidence to support this evidence is low according to the GRADE system. Conclusions: Current evidence is too weak to consider α-7 nAChR agonists as an effective add-on treatment to antipsychotics to enhance cognition and negative symptoms.